Coronary flow reserve in patients with heart failure with preserved ejection fraction - A. V. Mochula; K. V. Kop’eva; A. N. Maltseva; E. V. Grakova; M. O. Gulya; А. M. Gusakova; K. V. Zavadovsky (Российский кардиологический журнал)
Aim. To study the parameters of myocardial blood flow (MBF) and coronary flow reserve (CFR) in patients with heart failure (HF) with preserved ejection fraction and evaluate their relationship with the severity of HF.Material and methods. The study included 47 patients (men, 68,7%) aged 65,0 (58,0; 72,0) years with left ventricular ejection fraction of 62 (56; 67)% and coronary artery stenosis <50%. Serum levels of N-terminal pro-brain natriuretic peptide (NT-proBNP) were assessed by enzyme immunoassay. MBF and CFR values were assessed using cardiac single photon emission computed tomography.Results. Depending on NT-proBNP levels, the patients were divided into 2 groups (p<0,001): the 1st group included (n=15) patients with NT-proBNP <125 pg/ml (58,2 [41,6; 70,7] pg/ml), while in the 2nd group (n=32) — with NT-proBNP ≥125 pg/ml (511,4 [249,8; 1578,1] pg/ml). The group of patients with high NTproBNP levels was characterized by higher values (by 33,8%, p=0,0001) of resting MBF and reduced CFR (by 14,7%, p=0,001) compared with patients with normal NT-proBNP level: resting MBF — 0,65 (0,44; 0,79) vs 0,43 (0,30; 0,58) ml/min/g; CFR — 2,21 (1,52; 2,83) vs 2,59 (2,47; 3,05), respectively. At the same time, MBF at stress did not differ between the groups. The relationship of NTproBNP levels with global CFR (p=0,012; r=-0,339) and MBF at rest (p=0,012; r=0,322) was established. A stepwise decrease in global CFR was revealed depending on the NYHA class as follows (p<0,001): 2,79 (2,52; 2,93); 1,8 (1,55; 2,08); 1,31 (1,23; 1,49) — for class I, II, and III, respectively.Conclusion. A decrease in CFR in patients with HF with preserved ejection fraction indicates impaired myocardial blood supply, which, in this group of patients, is associated with microcirculatory changes. At the same time, the severity of MBF alterations is closely related to HF severity.